Pelatihan Basic Safety Management System Bagi Personel TNI AU Di Pangkalan Udara Atang Sendjaja - Imam Sonhaji; Supardam, Dhian; Nunuk Praptiningsih; Dwi Lestary; Tri Saputra, Surya; Wahyu Kurniawan; Ichyu Machiyana (Politeknik Penerbangan Indonesia Curug, 2025)
Safety Management System (SMS) is a term used to refer to a comprehensive business management system designed to manage safety factors in the workplace. SMS provides a systematic way to identify hazards and manage risks to ensure effective risk management. Every aviation service provider is required to create, implement, evaluate, and continuously improve a safety management system based on the national aviation safety program. SMS describes the scope and application for aviation service providers. As part of the aviation personnel, of course, TNI AU personnel at the Atang Sendjaja TNI AU Base need knowledge about safety to be ready to work. To improve understanding of the Safety Management System, the Indonesian Aviation Polytechnic Curug held a community service activity in the form of Basic Safety Management System Training for TNI AU Personnel at the Atang Sendjaja TNI AU Base. The training was carried out offline in class with the method used not only lectures but also group discussions and ice breaking. The results of this training showed that there was an increase in personnel's understanding of safety, strengthening of safety culture and increasing awareness and skills in terms of safety management.